2016
DOI: 10.1302/0301-620x.98b1.36409
|View full text |Cite
|
Sign up to set email alerts
|

The modern, hybrid total hip arthroplasty for primary osteoarthritis at the Hospital for Special Surgery

Abstract: We describe our technique and rationale using hybrid fixation for primary total hip arthroplasty (THA) at the Hospital for Special Surgery. Modern uncemented acetabular components have few screw holes, or no holes, polished inner surfaces, improved locking mechanisms, and maximised thickness and shell-liner conformity. Uncemented sockets can be combined with highly cross-linked polyethylene liners, which have demonstrated very low wear and osteolysis rates after ten to 15 years of implantation. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…That was the reason why the use of the cemented acetabular cups has decreased 161718). By comparison, the cemented femoral component is still being used in many cases, and has revealed favorable clinical performance for more than 15 years as the concept of hybrid THA192021). This is because that this component has secured satisfying durability along with improvements in cemented femoral component designs and cementing techniques.…”
Section: Cemented Vs Cementless Hip Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…That was the reason why the use of the cemented acetabular cups has decreased 161718). By comparison, the cemented femoral component is still being used in many cases, and has revealed favorable clinical performance for more than 15 years as the concept of hybrid THA192021). This is because that this component has secured satisfying durability along with improvements in cemented femoral component designs and cementing techniques.…”
Section: Cemented Vs Cementless Hip Arthroplastymentioning
confidence: 99%
“…And cementing techniques have a low risk of complications associated with cementless THA such as periprosthetic fracture and thigh pain19). Currently, cementless THA is predominantly performed because of the rapid progression of cementless design, shorter operating time, and technical difficulties of cementing23).…”
Section: Cemented Vs Cementless Hip Arthroplastymentioning
confidence: 99%
“… 1 This suggests that a taper slip design with a polished finish stem enables cement creep and are less prone to mechanical failure than rough surface stems. 2 - 4 Reported outcomes are generally more favourable for cement thicknesses of at least 2 mm, and this thickness is now widely accepted as optimum for the cement mantle. 5 - 7 However, some reports have suggested that French-designed cemented stems are associated with favourable outcomes in the presence of a thin cement mantle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, preoperative radiographs and intraoperative findings were assessed to classify tibial and femoral bone loss according to the Anderson Orthopaedic Research Institute (AORI) bone defect classification (Table 3 ) . The Knee Society Score (KSS) [ 16 ], the Hospital for Special Surgery (HSS) Knee Score [ 17 ], and range of motion (ROM) [ 18 ] were also collected.…”
Section: Methodsmentioning
confidence: 99%